The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pat.5269
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of poly(3‐methacryloylamido propyl trimethyl ammonium chloride) initiated by different initiators

Abstract: The poly(3-methacryloylamido propyl trimethyl ammonium chloride) (PMAPTAC) was synthesized by radical polymerization in aqueous solution polymerization using ammonium persulfate (APS) and 2,2 0 -azobis(2-methylpropionamide) dihydrochloride (V50) as initiator, respectively. The kinetics of polymerization were examined by changing various monomer and initiator concentrations via the dilatometer method at a low conversion level. The results showed that the polymerization rate grew with increasing monomer, initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…It could be seen that the infrared absorption spectrum of PAC/PMAPTAC and PAC/PDMDAAC were not much different from that of PAC, there was no evidence of chemical reaction between polyaluminum and polymers. However, it could be seen that the PAC/PMAPTAC had the same peaks as PMAPTAC at 1530 and 1481 cm À1 , which were attributed to the asymmetric stretching vibration of the N H in the amide group and the methyl group in the quaternary ammonium group in PMAPTAC, 26 indicating the existence of PMAPTAC in composite. PAC/PDMDAAC had an absorption peak of flexural vibration similar to PDMDAAC at 1469 cm À1 , which was attributed to the asymmetric stretching vibration of the CH 3 group in PDMDAAC, 27 indicating the existence of PDMDAAC in composite.…”
Section: Flocculation Testmentioning
confidence: 94%
See 3 more Smart Citations
“…It could be seen that the infrared absorption spectrum of PAC/PMAPTAC and PAC/PDMDAAC were not much different from that of PAC, there was no evidence of chemical reaction between polyaluminum and polymers. However, it could be seen that the PAC/PMAPTAC had the same peaks as PMAPTAC at 1530 and 1481 cm À1 , which were attributed to the asymmetric stretching vibration of the N H in the amide group and the methyl group in the quaternary ammonium group in PMAPTAC, 26 indicating the existence of PMAPTAC in composite. PAC/PDMDAAC had an absorption peak of flexural vibration similar to PDMDAAC at 1469 cm À1 , which was attributed to the asymmetric stretching vibration of the CH 3 group in PDMDAAC, 27 indicating the existence of PDMDAAC in composite.…”
Section: Flocculation Testmentioning
confidence: 94%
“…The peaks at 971, 1481, 1529, and 1644 cm À1 in curve of PMAPTAC were attributed to N + (CH 3 ) 3 , CH 3 in the quaternary ammonium group, N H and C═O groups in PMAPTAC, respectively. 26 The adsorption peaks at 3016 and 1467 cm À1 were assigned to the antisymmetric stretching vibration and bending vibration of the methyl groups in PDMDAAC, respectively, the absorption peak at 2936 cm À1 was the C H bond in the methyl group in PDMDAAC for antisymmetric stretching formed by vibration. 27 The Figure 1a verified the successful synthesis of PDMDAAC and PMAPTAC.…”
Section: Flocculation Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Losada et al 16–18 examined the impact of strong electrostatic interactions of doubly charged quaternary ammonium salts on free radical solution polymerization, and they found that the chemical structure of the cationic monomer, particularly the location of the ionic group, significantly impacted the polymerization reactivity of the monomer. Wang et al 19 examined the polymerization kinetics of MAPTAC initiated by ammonium persulfate (APS) and 2,2′‐azobis(2‐methylpropionamide) dihydrochloride (V50). The polymerization activation energies under the given conditions were E aV = 144.76 kJ/mol and E aA = 153.09 kJ/mol, respectively.…”
Section: Introductionmentioning
confidence: 99%